Wives of Los Alamos - Nesbit, TaraShea (Thorndike, Maine Center Point Large Print, 2014)
Their average age was twenty-five. They came from Berkeley, Cambridge, Paris, London and Chicago and arrived in New Mexico ready for adventure--or at least resigned to it. But hope quickly turned to hardship in the desolate military town where everything was a secret--including what their husbands were doing at the lab. They lived in barely finished houses with a P.O. Box for an address, in a town wreathed with barbed wire, all for the benefit of "the project" that didn't exist as far as the greater world was concerned. They were constrained by words they couldn't say out loud, the letters they couldn't send home, the freedom they didn't have. Though they were strangers, they joined together. Babies were born, friendships were forged and children grew up. But then "the project" was unleashed and even bigger challenges faced the women of Los Alamos, as they struggled with the burden of their contribution towards the creation of the most destructive force in mankind's history--the atomic bomb. Contentious, gripping and intimate, The Wives of Los Alamos is a personal tale of one of the most momentous events in our history.
101668
Keywords: Married women -- New Mexico -- Los Alamos; World War -- New Mexico -- Los Alamos -- 1939-1945; Deception (Military science) -- History -- 20th century; Atomic bomb; Large type books; Los Alamos (N.M.); New Mexico -- Los Alamos; Historical fiction; Suspense fiction; War stories; Fiction; History